2014
DOI: 10.7567/apex.7.062702
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency watt-level 1014 nm single-frequency laser based on short Yb-doped phosphate fiber amplifiers

Abstract: Atomic layer deposition coatings are under investigation to reduce the diffusion of radioxenon into plastic scintillators. This paper investigates the impact of such surface coating on the light collection efficiency in a cylindrical geometry. A high and uniform light collection efficiency is important to preserve detector resolution. Monte Carlo simulations and measurements have been carried out to study the influence of coating thickness, refractive index and surface quality. It was found that it is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…A compact fiber laser of 5 mm was reported, with a CW single transverse and longitudinal mode characterized by an output power over 164 mW, low noise and a linewidth lower than 7 kHz. At the wavelength of 1014 nm Yang et al [76] reported also a MOPA laser with over 1 W of single-frequency emission, obtained by amplifying a seed laser with a core-pumped one stage Yb 3+ -doped phosphate fiber amplifier of 4 cm of length.…”
Section: Yb-doped Single-frequency Phosphate Fiber Lasersmentioning
confidence: 99%
“…A compact fiber laser of 5 mm was reported, with a CW single transverse and longitudinal mode characterized by an output power over 164 mW, low noise and a linewidth lower than 7 kHz. At the wavelength of 1014 nm Yang et al [76] reported also a MOPA laser with over 1 W of single-frequency emission, obtained by amplifying a seed laser with a core-pumped one stage Yb 3+ -doped phosphate fiber amplifier of 4 cm of length.…”
Section: Yb-doped Single-frequency Phosphate Fiber Lasersmentioning
confidence: 99%
“…The fibre reported in this Letter can be applicable in demanding high quality beam compact devices but also, due to the large core, in pulsed laser solutions that are power-limited by nonlinear effects [2]. Our fibre can also find application as a laser seed due to the possibility of achieving low noise and single-frequency operation if used with narrow linewidth fibre Bragg grating [19][20][21] or as an amplifying stage in a laser system [22,23].…”
Section: Discussionmentioning
confidence: 95%
“…With developing semiconductor lasers, ytterbium (Yb 3+ ) is the most suitable ion of luminescent active ions for high power laser because of its small quantum defect and simple energy level [1][2][3][4][5][6]. Due to the high solubility of Yb 3+ in phosphate glass [7], it is expected that it will be used in high-gain, short-length solid-state systems, such as single frequency lasers [8][9][10][11]. However, the narrow Stark splitting of the Yb 3+ : 2 F7/2 level leads to a serious thermal blocking effect in solid-state Yb: phosphate glass lasers [12].…”
Section: Introductionmentioning
confidence: 99%